Isolated nocturnal hypertension in pediatric kidney transplant recipients. (29th November 2021) - Seeman, Tomáš; Pfaff, Mairead; Sethna, Christine B.
Abstract: Background: Isolated nocturnal hypertension (INH) is defined as nighttime hypertension in the setting of normal daytime blood pressure (BP), diagnosed by ambulatory BP monitoring (ABPM). Methods and Results: Hypertension affects 60%–80% of pediatric kidney transplant recipients, and INH is the most common type of ambulatory hypertension. INH is associated with an increased prevalence of hypertension‐mediated target organ damage such as left ventricular hypertrophy in adults and in pediatric kidney transplant recipients. Conclusion: Ambulatory BP monitoring should be performed annually in all pediatric kidney transplant recipients to diagnose hypertension phenotypes that are not detectable by office BP such as masked hypertension, white‐coat hypertension, or INH. Isolated nocturnal hypertension in pediatric transplant patients requires study as a treatment target.